Novel Predictive Nomogram for Identifying Difficult Guidewire Insertion in Patients With Malignant Colorectal Obstruction and Sphincterotome-Assisted Guidewire Insertion for Improving the Success Rate of Self-Expandable Metal Stent Insertion - Zhu, Zhenhua; Li, Biming; Liao, Wangdi; Lv, Nonghua; Chen, Youxiang; Shu, Xu (Frontiers in Oncology, 2020)
Aims: This study aimed to identify risk factors related to guidewire insertion (GWI) failure and construct a novel predictive nomogram. In addition, sphincterotome-assisted guidewire insertion (SAGWI) in difficult cases was evaluated for efficacy and safety. Methods: We reviewed the data of 509 patients with malignant colorectal obstruction who underwent endoscopic self-expandable metal stent (SEMS) insertion from 2007 to 2018 in our center, retrospectively. We identify risk factors associated with GWI failure by multivariate logistic regression analysis and construct a novel predictive nomogram. Improvements in the GWI and technical and clinical success rates were assessed for the SAGWI technique. Results: A total of 509 patients with malignant colorectal obstruction were included. Increases of 6.9% and 7.0% were found in the GWI success rate by intention-to-treat (ITT; p < 0.001) and per-protocol (PP; p < 0.001) analyses after SAGWI, respectively. Increases of 6.5% and 6.6% in the technical success rate were found by ITT (p < 0.001) and PP (p < 0.001) analyses after SAGWI, respectively. Increases of 5.8% and 6.0% in the clinical success rate were found by ITT (p < 0.001) and PP (p < 0.001) analyses after SAGWI, respectively. Regarding the GWI failure-related factors, a sharply angulated stricture was an independent risk factor, and an experienced colonoscopist was an independent protective factor. A novel effective predictive nomogram was constructed. Conclusion: The novel predictive nomogram can be conveniently used to identify difficult cases. A sharply angulated stricture and an experienced colonoscopist are independent factors related to GWI failure. The SAGWI technique is an effective and safe method for addressing technically difficult cases.